2012
DOI: 10.1111/1440-1630.12017
|View full text |Cite
|
Sign up to set email alerts
|

Towards a definition of professionalism in Australian occupational therapy: Using the Delphi technique to obtain consensus on essential values and behaviours

Abstract: The results provide insight into several professional values and behaviours perceived as essential for practice. Consequently, these professional values need to be taken into consideration when defining the values of the profession. The professional behaviours need to be taken into account when finalising the essential behaviours that constitute professionalism in the profession. This study takes an initial but fundamental step towards defining professionalism within the Australian occupational therapy profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 33 publications
1
54
0
7
Order By: Relevance
“…As reported in Aguilar et al (2013b), 51 values emerged as essential in the first occupational therapy Delphi questionnaire. Sixty-three occupational therapy participants completed the second Delphi questionnaire (93% retention rate) and 81% of these participants indicated that the 51 values were all the values that were essential lor practice.…”
Section: Delphi Phasementioning
confidence: 91%
See 1 more Smart Citation
“…As reported in Aguilar et al (2013b), 51 values emerged as essential in the first occupational therapy Delphi questionnaire. Sixty-three occupational therapy participants completed the second Delphi questionnaire (93% retention rate) and 81% of these participants indicated that the 51 values were all the values that were essential lor practice.…”
Section: Delphi Phasementioning
confidence: 91%
“…physiotherapy or occupational therapy). In the second phase, the values identified through the interviews were presented to a broad range of occupational therapy and physiotherapy professionals via Delphi questionnaires, in order to identify the values that they perceived as essential for practice (Aguilar, Stupans, Scutter, & King, 2013b). Both phases of the study have the potential to assist these two professions with identifying and articulating their values.…”
Section: Introductionmentioning
confidence: 99%
“…Lorsque l'on s'intéresse aux valeurs de l'ergothérapie [1,3,[11][12] et à celles des ergothérapeutes [4][5][6][7][8][13][14][15], force est de constater que la valeur qu'est la santé est certes valorisée dans la profession et par les ergothérapeutes, mais dans une moindre mesure que d'autres valeurs reliées à l'occupation humaine (comme la participation occupationnelle, l'engagement occupationnel, la signifiance occupationnelle, l'équilibre occupationnel et la justice occupationnelle). En effet, lorsqu'on interroge des ergothérapeutes sur leurs valeurs professionnelles, et ce, peu importe leur nationalité, la vaste majorité d'entre eux accorde plus d'importance à la participation occupationnelle (c'est-à-dire au fait pour les patients de prendre part aux activités qui sont importantes pour eux et qui donnent un sens à leur existence) qu'elle n'en accorde à la santé [4,[13][14][15].…”
Section: Valeurs Professionnelles De L'ergothérapie Et Des Ergothérapunclassified
“…En effet, lorsqu'on interroge des ergothérapeutes sur leurs valeurs professionnelles, et ce, peu importe leur nationalité, la vaste majorité d'entre eux accorde plus d'importance à la participation occupationnelle (c'est-à-dire au fait pour les patients de prendre part aux activités qui sont importantes pour eux et qui donnent un sens à leur existence) qu'elle n'en accorde à la santé [4,[13][14][15]. C'est que la profession ergothérapique est davantage liée à l'autonomie et au bien-être des patients qu'à leur santé proprement dite.…”
Section: Valeurs Professionnelles De L'ergothérapie Et Des Ergothérapunclassified
“…Occupational therapists interact with a variety of individuals who occupy different roles, making professionalism a pre-requisite for successful and effective interactions in practice (Aguilar, Stupans, Scutter & King, 2012;Fidler, 1996). Current literature highlights the need for profession-specific understanding of professionalism due to the inherent differences between professions, such as values, legal frameworks, and ethics (Aguilar, Stupans, Scutter & King, 2013;Bryden et al, 2010;McNair, 2005;Robinson et al, 2012). This diversity accounts for a degree of the variability that exists between professions and why professionalism 'definitions' may not be transferable, thus, reinforcing the need for explicit discussions of professionalism within the field of occupational therapy (Aguilar, Stupans, Scutter & King, 2014).…”
Section: Introductionmentioning
confidence: 99%